Sensitivity of Very Small Glaciers in the Swiss Alps to Future Climate Change - Huss, Matthias; Fischer, Mauro (Frontiers in Earth Science, 2016)
Very small glaciers (<0.5 km2) account for more than 80% of the total number of glaciers in mid- to low-latitude mountain ranges. Although their total area and volume is small compared to larger glaciers, they are a relevant component of the cryosphere, contributing to landscape formation, local hydrology and sea-level rise. Worldwide glacier monitoring mostly focuses on medium-sized to large glaciers leaving us with a limited understanding of the response of dwarf glaciers to climate change. In this study, we present a comprehensive modeling framework to assess past and future changes of very small glaciers at the mountain-range scale. Among other processes our model accounts for snow redistribution, changes in glacier geometry and the time-varying effect of supraglacial debris. It computes the mass balance distribution, the englacial temperature regime and proglacial runoff. The evolution of 1,133 individual glaciers in the Swiss Alps is modeled in detail until 2060 based on new distributed data sets. Our results indicate that 52% of all very small glaciers in Switzerland will completely disappear within the next 25 years. However, a few avalanche-fed glaciers at low elevation might be able to survive even substantial atmospheric warming. We find highly variable sensitivities of very small glaciers to air temperature change, with gently-sloping, low-elevation, and debris-covered glaciers being most sensitive.